Updated Evaluation of Agalsidase Alfa Enzyme Replacement Therapy for Patients with Fabry Disease: Insights from Real-World Data - Feriozzi S; Chimenti C; Reisin RC (Dove Medical Press, 2024)
Sandro Feriozzi,1 Cristina Chimenti,2 Ricardo Claudio Reisin3 1Department of Nephrology and Dialysis Unit, Belcolle Hospital Viterbo, Italy; 2Department of Clinical Sciences, Internal Medicine, Anesthesiology and Cardiovascular Sciences, La Sapienza University, Rome, Italy; 3Department of Neurology, Hospital Británico, Buenos Aires, ArgentinaCorrespondence: Sandro Feriozzi, Nephrology and Dialysis Unit, Belcolle Hospital, Strada Sammartinese snc, Viterbo, 01100, Italy, Tel +39/0761338602, Fax +39/076133600, Email sandro.feriozzi@gmail.comAbstract: The clinical use of agalsidase alfa as enzyme replacement therapy (ERT) for Fabry disease (FD) has spread since 2001, and a large body of evidence of its effectiveness has been collected. This review presents the clinical and laboratory results achieved with agalsidase alfa, which has been published in the literature. Agalsidase alfa infusion slows down or stops the progression of renal damage, expressed by reduction or stabilization of the annual decline of the glomerular filtration rate; yearly decrease of glomerular filtration rate (slope) sometimes is reduced until its stabilization. ERT prevents or reduces the occurrence of hypertrophic cardiomyopathy or slows the increase over time if it is already present. Moreover, regarding neurological manifestations, ERT improves neuropathic pain and quality of life, and recent data indicated that it may also prevent the burden of cerebrovascular disease. In addition to ERT's clinical benefits, crucial topics like the most appropriate time to start therapy and the role of anti-drug antibodies (ADA) are analyzed. Treatment with agalsidase alfa in patients with FD substantially improves their outcomes and enhances their quality of life in patients with FD.Keywords: Fabry disease, agalsidase alfa, enzyme replacement therapy, clinical outcome in Fabry treated patients